Isolated and nilpotent subsemigroups in the variants of ISn - Tsyaputa, G. (Algebra and Discrete Mathematics, 2006)
All isolated, completely isolated, and nilpotent
subsemigroups in the semigroup ISn of all injective partial transformations of an n-element set, considered as a semigroup with a
sandwich multiplication are described.